Perda Mandailing Natal Pasal 7 No.4 Tahun 2010 - Marcelliani, Marcelliani (Jurnal El-Thawalib, 2022)
Many traders who sell in the old Panyabungan market resulted in some of the traders selling their wares on the sidewalk. Meanwhile, this act will disturb the comfort of every sidewalk user. The problem formulation of the author is how to implement article 7 of the Mandailing Natal district regulation no. 4 of 2010 concerning business order in the old Panyabungan market and how to review fiqhsiyasah on the implementation of Article 7 of the Mandailing Natal Regency Regional Regulation No. 4 of 2010 concerning orderly business in the old Panyabungan market. While the purpose of the study was to determine the implementation of Article 7 of the Mandailing Natal District Regulation No. 4 of 2010 concerning orderly business in the old market of Panyabungan, Mandailing Natal district, and to find out the fiqhsiyasah review of business order in the old market of Panyabungan, Mandailing Natal district. The type of research used in this research is field research, namely the author will go directly to the field to examine a problem, the data used are primary and secondary data, the method of collecting data is the direct interview method. The results of this study are orderly business in the old market Panyabungan, Mandailing Natal district, namely street vendors are prohibited from trading on the sidewalk, because their activities are very disturbing to pedestrians, and the implementation is carried out by the PP Satpol by giving warnings or conducting raids. against street vendors not to sell on the sidewalk.